Economy and ethnic entrepreneurship: a historic summation of the experience in the state of São Paulo - Truzzi, Oswaldo Mário Serra (2007)
This paper relates two distinct themes: entrepreneurship and ethnicity. They are normally treated by different academic traditions: economists and businessmen deal with the fi rst, while anthropologists, sociologists and historians usually investigate the latter. Due to the recent development of areas like Organizational Culture and Economic Sociology, approximations between these two themes have occurred, allowing a conjoint treatment of them in the fi eld defi ned as ethnic entrepreneurship. Studies in this new area recognize that many resources and job possibilities for immigrants are available at their own communities, where networks of social capital pervade. More than driving defi nite conclusions, this work explores some insights in this area, taking São Paulo’s historical socio-economic experience as reference.